Performance of Cassava, Sweet Potato and Chinese Potato in Rice Based Cropping Systems of Southern Kerala - John, Jacob; Bhasuran, Rani; Varughese, Kuruvilla; Mathew, Babu (JOURNAL OF ROOT CROPS, 2015)
A five year field study was undertaken in the wetland rice fields of Cropping Systems Research Centre, Kerala Agricultural University, Thiruvananthapuram during 2006 virippu/kharif to 2011 summer. The treatments were eight rice based cropping sequences viz., T1: rice-rice-fallow, T2: rice-rice sweet potato (var. Kanhangad), T3: rice-rice-pumpkin (var. Ambili), T4: rice-rice-sesamum (var. Thilarani), T5: rice-rice-amaranthus (var. Arun), T6: rice-rice-vegetable cowpea (var. Vellayani local), T7: rice-Chinese potato (var. Nidhi)-daincha, T8: rice-cassava (var. Vellayani Hraswa)-daincha. The experiment was laid out in randomized block design and treatments were replicated thrice. The performance of the crops over the years was analysed through the stability index (based on yield). The economics of cultivation was also worked out. From the stability analysis, ancillary observations and economic analysis over the past five years (2006-2011), it can be concluded that rice-rice-amaranthus and rice-rice-sweet potato were the best cropping sequences. This is followed by rice-rice-cowpea and rice-rice-pumpkin. The sequences, rice-rice-sesamum and rice-Chinese potato-daincha were not suitable for southern Kerala. Stability index for Chinese potato was very low.